IL-13 Augments Histone Demethylase JMJD2B/KDM4B Expression Levels, Activity, and Nuclear Translocation in Airway Fibroblasts in Asthma - Khuloud Bajbouj; Mahmood Y. Hachim; Rakhee K. Ramakrishnan; Huwaida Fazel; Jumana Mustafa; Shahed Alzaghari; Mahmoud Eladl; Jasmin Shafarin; Ronald Olivenstein; Qutayba Hamid (Journal of Immunology Research)
Purpose. Asthma is one of the most common obstructive pulmonary diseases worldwide. Epigenetic alterations, including DNA methylation and histone modifications, have been reported to contribute to asthma pathogenesis. Since the inflammation mediator and remodeling trigger, IL-13, is known to play a central role in the pathophysiology of asthma, this study was aimed to identify novel IL-13-regulated epigenetic modifiers in asthma that may contribute to subepithelial fibrosis. Methods. Publicly available transcriptomic datasets from Gene Expression Omnibus (GEO) were used to identify differentially expressed genes on an epigenetic level upon IL-13 exposure in lung fibroblasts. Bronchial fibroblasts isolated from healthy and asthmatic individuals were assessed for the gene and protein expression levels of the identified gene at baseline and upon IL-13 treatment using qRT-PCR and western blotting, respectively. Its subcellular localization and tissue distribution were examined in bronchial fibroblasts as well as bronchial biopsies by immunofluorescence and immunohistochemical analysis, respectively. Results. Bioinformatic analysis revealed the differential expression of the histone demethylase JMJD2B/KDM4B, a well-known epigenetic modulator that leads to the demethylation of different lysine residues on histones, in IL-13-treated lung fibroblasts. The baseline expression levels of JMJD2B were higher in asthmatic fibroblasts and in bronchial biopsies in comparison to healthy ones. There was also an increase in JMJD2B activity as evidenced by the demethylation of its downstream target, H3K36me3. Furthermore, IL-13 stimulation induced JMJD2B expression and further demethylation of H3K36me3 in asthmatic fibroblasts. This was accompanied by increased translocation of JMJD2B into the nucleus. Conclusion. This study highlights the novel pathological involvement of the histone demethylase JMJD2B/KDM4B in asthmatic airway fibroblasts that are regulated by IL-13. Clinical implications. Given that there is no single therapeutic medicine to effectively treat the various subtypes of asthma, this study provides promising insights into JMJD2B as a new therapeutic target that could potentially improve the treatment and management of asthma.